ANALISIS DAMPAK COMPONENT COMMONALITY TERHADAP SCHEDULE INSTABILITY PADA SISTEM RANTAI PASOK SEDERHANA - Bilal Ahmadi; Dhany Surya Ratana (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
This study analyzed the impact of component commonality to schedule instability. Analysis was implemented in the use of component commonality (use of same component in different product structures) in a simple supply chain system which is consist of one manufacturer and two suppliers. Different operational conditions were introduced such as: demand uncertainty, product cost structure, product lead time, product structure and inventory policy that company utilized. The simulation results suggested that common component could reduce schedule instability in both manufacturer and suppliers. Furthermore, the results also indicated that suppliers were the more affected entities due to uncertainty rather than manufacturer